Associations of education with 30 year life course blood pressure trajectories: Framingham Offspring Study - Xiao Yongling; Abrahamowicz Michal; Loucks Eric B; Lynch John W (BMC, 2011)
Abstract Background Education is inversely associated with cardiovascular disease incidence in developed countries. Blood pressure may be an explanatory biological mechanism. However few studies have investigated educational gradients in longitudinal blood pressure trajectories, particularly over substantial proportions of the life course. Study objectives were to determine whether low education was associated with increased blood pressure from multiple longitudinal assessments over 30 years. Furthermore, we aimed to separate antecedent effects of education, and other related factors, that might have caused baseline differences in blood pressure, from potential long-term effects of education on post-baseline blood pressure changes. Methods The study examined 3890 participants of the Framingham Offspring Study (mean age 36.7 years, 52.0% females at baseline) from 1971 through 2001 at up to 7 separate examinations using multivariable mixed linear models. Results Mixed linear models demonstrated that mean systolic blood pressure (SBP) over 30 years was higher for participants with ≤12 vs. ≥17 years education after adjusting for age (3.26 mmHg, 95% CI: 1.46, 5.05 in females, 2.26 mmHg, 95% CI: 0.87, 3.66 in males). Further adjustment for conventional covariates (antihypertensive medication, smoking, body mass index and alcohol) reduced differences in females and males (2.86, 95% CI: 1.13, 4.59, and 1.25, 95% CI: -0.16, 2.66 mmHg, respectively). Additional analyses adjusted for baseline SBP, to evaluate if there may be educational contributions to post-baseline SBP. In analyses adjusted for age and baseline SBP, females with ≤12 years education had 2.69 (95% CI: 1.09, 4.30) mmHg higher SBP over follow-up compared with ≥17 years education. Further adjustment for aforementioned covariates slightly reduced effect strength (2.53 mmHg, 95% CI: 0.93, 4.14). Associations were weaker in males, where those with ≤12 years education had 1.20 (95% CI: -0.07, 2.46) mmHg higher SBP over follow-up compared to males with ≥17 years of education, after adjustment for age and baseline blood pressure; effects were substantially reduced after adjusting for aforementioned covariates (0.34 mmHg, 95% CI: -0.90, 1.68). Sex-by-education interaction was marginally significant (p = 0.046). Conclusion Education was inversely associated with higher systolic blood pressure throughout a 30-year life course span, and associations may be stronger in females than males.